Comparing the Effects of a Herbal Ointment (Based on Persian Medicine) and Silver Sulfadiazine Ointment on the Second-Degree Burn Wounds: a Single-Blind Randomized Clinical Trial - Mehdi Alizadeh; Mostafa Dahmardehei; Shirin Fahimi; Sajjad Sadeghi; Roshanak Mokaberinejad* (Iranian Society of Pharmacognosy, 2020)
Background and Objective: Burn injuries impose heavy costs on the healthcare systems. Since the available treatments for burn injuries are costly and have several complications, the present study aimed to compare the effects of an Iranian traditional medicine product in the form of a herbal ointment with silver sulfadiazine ointment on second-degree burn wounds. Methods: In this single-blind randomized clinical trial, the patients were divided into two groups of herbal ointment (Rosa damascena, Solanum nigrum, and Malva sylvestris) and SSD ointment (control). They were evaluated in terms of improvement, wound closure, wound appearance, and intervention complications prior to the treatment, on the fourth day, and after 1-4 weeks. Results: Fifty three participants completed the trial (27 in herbal ointment and 26 in SSD group). The mean burn wound healing time was 11.58±5.36 and 16.80±5.60 days in the herbal and SSD groups, respectively, which showed a significant difference in this regard (p=0.001). Moreover, the wound closure percentage in the first two weeks was significantly higher in the herbal group compared to the SSD group (p <0.05). Also, wound appearance was better in the herbal ointment group in all the assessment times. No significant difference was observed between the herbal and SSD ointment regarding the treatment complications. Conclusion: The herbal ointment containing Rosa damascena, Malva sylvestris, and Solanum nigrum showed more considerable effects on the second-degree burn wounds compared to the SSD ointment.